Legal Protections for Disabled Child Victims of Sexual Violence in Sidoarjo, Indonesia: Perlindungan Hukum bagi Anak Penyandang Disabilitas Korban Kekerasan Seksual di Sidoarjo, Indonesia - Perta Wida Subastian; Emy Rosnawati (Academia Open, 2023)
This study probes the legal safeguards available for children with disabilities subjected to sexual violence in Sidoarjo Regency, Indonesia, adopting a normative juridical approach. Using normative legal research methodologies, the data collection was conducted through document studies and legal document analysis concerning the legal protection of children and people with disabilities. The research unveiled that the Child Protection Law No. 35/2014 provides special regulations for the protection of children with disabilities, yet it does not explicitly address sexual violence. Conversely, the Disability Law No. 8 of 2016 expressly outlines the rights of disabled children against sexual abuse and their entitlement to education. The study also found congruity in the TPKS Law No. 12 of 2022, which stipulates the protection of disabled children subjected to sexual violence during legal proceedings. The results imply the potential for improved preventive measures, such as local regulations in Sidoarjo Regency addressing sexual violence against disabled children, proactive parental supervision, and a call for societal protection of these children. Furthermore, the implementation of strict sanctions as per applicable laws may provide a sense of justice for the victims.Highlights: Child Protection Law No. 35/2014 and Disability Law No. 8 of 2016 together address the protection of children with disabilities, albeit without explicit mention of sexual violence in the former. The TPKS Law No. 12 of 2022 provides a specific legal framework for the protection of disabled children who are victims of sexual violence during court proceedings. Preventive measures and stringent sanctions, as per these laws, could provide an enhanced sense of justice and security for victims, underscoring the necessity of societal vigilance and parental involvement. Keywords: Legal protection, Children with disabilities, Sexual violence, Indonesia, Normative juridical approach